Pandangan Mahasiswa Universitas Teknologi Sumbawa Terkait Simbol Dalam Standar Kecantikan - Syofyan Aldy Wijaya; Topan Rahmatul Iman (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Human perception of beauty is different, beauty is the dream of every woman, both teenagers and children from an early age. so this study aims to determine the views of Sumbawa University of Technology students on beauty. This research uses qualitative research methods and the basic type of qualitative description with data collection techniques in the form of interviews and documentation. This study was conducted within the environment of Sumbawa University of Technology. Interviews and documentation were used as data collection techniques. Using Pride and Farrel's Perception, perception is all the processes by which information is retrieved, organized, interpreted and communicated. This can be seen from one's opinion about beauty standards. Because female beauty is not only physical, but one's personality and intelligent behavior, can be said to be a measure of beauty.